Topical Lidocaine Gel Versus Tetracaine Eye Drops for Panretinal Photo-coagulation in Proliferative Diabetic Retinopathy - Ade J. Nursalim; Vera Sumual; Andrew Chietra; Christian Komaling; Stevanus Loho; Ardelia E. Wulur (Medical Scope Journal, 2024)
Panretinal photocoagulation (PRP) is a treatment for proliferative diabetic retinopathy (PDR). The procedure needs anesthetic agent to overcome the pain. Two widely used anesthetic agents are used in this study which are tetracaine 0.5% eyedrops and lidocaine 2% gel. This study aimed to compare the effectivity and efficacy of both anesthetic agents. A prospective randomized controlled trial was done to 40 eyes divided into two groups, group A was treated with tetracaine 0.5% eyedrop and group B with lidocaine 2% gel. Pain score was obtained subjectively from the patient and recorded during four stages of procedure. The results showed that the mean age was 56.5 years in Group A and 53.20 years in group B. Average procedure duration was 8.7 minutes in group A and 9.35 minutes in group B. Average 5 minutes pain level was 3.05 and 2.10 in group A and B consecutively. Average 10 minutes pain level was 2.65 and 2.45 in group A and B consecutively. Average during procedure pain level was 2.70 and 3.40 in group A and Group B, and average post procedure pain level was 1.20 in Group A and 1.55 in Group B. There was no significant difference between both groups’ parameters. In conclusion, the use of both agents is interchangeable and shows no differences in efficacy and effectivity. Keywords: panretinal photocoagulation; proliferative diabetic retinopathy; anesthetic agent; tetracaine; lidocaine